KEDUDUKAN WANITA DALAM ISLAM (Telaah Hadis-hadis Misoginis Menurut Moenawar Chalil): (Telaah Hadis-hadis Misoginis Menurut Moenawar Chalil) - Alfani, Mukhammad; Badrut Tamam, Moh Hilmi; Muhid, Muhid; Atim Muthoharoh, Isnaini Lu'lu' (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
This research focuses on the examination of traditions considered misogynistic by Moenawar Chalil to study the position of women in Islam. The role and rights of women in religion often become a complex debate in modern, increasingly advanced societies. This research aims to broaden the author's understanding of Moenawar Chalil's thoughts on the controversial hadiths related to women in Islam in the book The Value of Women as the main reference. This study uses qualitative analysis as well as library research from several books, journals, and documents. This study shows that Moenawar Chalil takes a critical approach to the traditions that are considered misogynistic and puts forward his perspective in responding to the hadith in his era. The study also found that Moenawar Chalil provides an important perspective for understanding the position of women in Islam. He shows that Islam truly supports gender equality and many traditions that are considered misogynistic can be interpreted in a way that is more appropriate to the current context. It is hoped that this study will provide a more accurate understanding of the position of women in Islam and Moenawar Chalil's thoughts on misogynistic traditions, or at least serve as an impetus for further study.